Al-Faraidl - Abu Yazid Adnan Quthny (Asy-Syari’ah : Jurnal Hukum Islam, 2019)
Al-Faraidl is a law of inheritance law in Islam originating from nash and ijtihad. This research is intended to examine the texts — both qathiy and dhanniy — and ijtihad with the library research approach, especially the review of the commentaries, hadith and ijtihad products (the efforts of friends and scholars in understanding / capturing the dhanniyas are from nash). The results of the review formulated that 25 heirs - whether from a marriage background, kinship or wala especially heirs who had selectively graduated from the hajb system - were divided into two categories, namely ash-al-furudl and ashabah. Al-furudl almuqaddarah — as patents of inheritance of ash-hab al-furudl — as many as six fardl, namely; 1/2, 1/3 (including 1/3 remaining), 2/3,¼, 1/6 and 1/8. Experts of inheritance of ashabah - who have the right to inherit the remainder of the fardl ash-hab al-furudl - are grouped into three parts, namely; bi an-nafs, bi al-ghair and maa al-ghair. Keyword: al-faraidl, nash, ijtihad.